Les aléas de la fraude en droit criminel - Rainville, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Even though section 338 Cr.C. appears in Part VIII of the Criminal Code entitled « Fraudulent transactions relating to Contracts and Trade », the criminal offence of fraud is of a much broader scope. The liberal interpretation received from the courts has transformed this crime into one of the widest and sometimes most unpredictable offences. The author first discusses Canada's territorial jurisdiction over international fraud in the light of the recent Libman case. He then proceeds to examine the impact of the Supreme Court decision in Vezina v. R. on the « deprivation » requirement in the definition of fraud. This text also concentrates on the objective-subjective mens rea dilemna and on a comparison of the constitutive elements of fraud, theft and false pretences. The author finally concludes that sections 320 and 338 Cr.C call out for immediate reform.